High-Dose Epidermal Radionuclide Therapy with 188Re (Rhenium) Resin in a Patient with Multiple Actinic Keratoses - Mirzaei, Siroos; Kunstfeld, Rainer (World Journal of Nuclear Medicine, 2024)
Aim High-dose epidermal radionuclide therapy using a nonsealed 188Re (Rhenium) resin is an alternative treatment option for nonmelanoma skin cancer. In this case study, we present the possible use of this therapy in a patient with multiple actinic keratosis (AK), which is a precancer of the skin.Methods A 55-year-old male was presented in our department with multiple AK, located on the cheek, temporal, and frontal area, with 1, 1, 2.1, and 2.5 cm2 surface.Applied activity was 80, 80, 167, and 168 MBq 188Re with a target absorbed dose for each lesion 35 Gy at 1 mm. The treatment was well tolerated.Results At 17 months’ follow-up, all treated area showed complete remission. There were no side effects, except mild focal hypopigmentation.Conclusion This case demonstrates the high potential of epidermal radionuclide therapy with a nonsealed 188Re as a noninvasive, effective, and well-tolerated therapy option for patients with multiple AK, when surgery is difficult to perform or not recommended of other reasons.
Keywords: actinic keratosis; epidermal therapy; radionuclide therapy; Rhenium-188; skin cancer